2013
DOI: 10.3390/w6010032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Version-7 TRMM Multi-Satellite Precipitation Analysis Product during the Beijing Extreme Heavy Rainfall Event of 21 July 2012

Abstract: Abstract:The latest Version-7 (V7) Tropical Rainfall Measuring Mission (TRMM) Multi-satellite Precipitation Analysis (TMPA) products were released by the National OPEN ACCESSWater 2014, 6 33Aeronautics and Space Administration (NASA) in December of 2012. Their performance on different climatology, locations, and precipitation types is of great interest to the satellite-based precipitation community. This paper presents a study of TMPA precipitation products (3B42RT and 3B42V7) for an extreme precipitation even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…MAE represents the averaged magnitude of the absolute error; RMSE indicates the averaged error magnitude; RB is used to measure the probability of overestimation (RB < 0) or underestimation (RB > 0) from satellite-based products; and CC reflects the synchronicity of precipitation variation between satellite precipitation products and meteorological stations. Compared with rain gauge data, the higher accuracy of satellite-based products has a higher CC, lower MAE, and RMSE [34]. Table 3.…”
Section: Categorical Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAE represents the averaged magnitude of the absolute error; RMSE indicates the averaged error magnitude; RB is used to measure the probability of overestimation (RB < 0) or underestimation (RB > 0) from satellite-based products; and CC reflects the synchronicity of precipitation variation between satellite precipitation products and meteorological stations. Compared with rain gauge data, the higher accuracy of satellite-based products has a higher CC, lower MAE, and RMSE [34]. Table 3.…”
Section: Categorical Statisticsmentioning
confidence: 99%
“…The Multi-Satellite Precipitation Analysis (TMPA) algorithm was proposed by Huffman et al [11] and it was combined with several other high-quality rainfall estimation algorithms, e.g., merged Active/Passive Microwave and Infrared-based rainfall estimates, as well as other multi-source data fusion of rainfall products [33]. The TMPA rainfall products are available both in 3B42RT (three-hourly) and 3B42 (three-hourly and daily), as well as the monthly rainfall dataset (3B43), covering the range of latitude 50 • S-50 • N and longitude 180 • W-180 • E. Compared to 3B42RT, 3B42V7 was corrected by the monthly rainfall data deviation from the Global Precipitation Climate Center (GPCC) calibration meteorological stations and the product has several computation improvements and a better data accuracy [34]. The most recent TRMM 3B42 Version 7 is a gauge-adjusted post-real-time rainfall product covering the 1998-present period from various satellite systems [11].…”
Section: Satellite-based Rainfall Productsmentioning
confidence: 99%
“…The current operational Version-7 TMPA system produces two standard user-level (Level 3) rainfall products at relatively fine resolution (0.25˝ˆ0.25˝, 3 h), i.e., the real-time 3B42RT (hereafter referred to as "RTV7"; 6-9 h after observation time) for the latitude band 60˝N-60˝S and the gauge-adjusted, post-real-time 3B42V7 for research purposes (hereafter "V7"; two months latency) with spatial coverage of 50˝N-50˝S [5,6]. Recently, these two quasi-global satellite precipitation products have been widely utilized in various hydrological and meteorological applications in China [7][8][9][10][11][12][13]. Over the years, there have been many efforts to compare and validate available satellite precipitation estimates at global, regional, or basin scales [9,10,[14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that there is a good agreement between the measured and estimated total monthly precipitation(R 2 = 0.98, p < 0.001). While satellite derived precipitation products have limitations in terms of accuracy and resolution for extreme rainfall events [25], it has been demonstrated that they produce reliable data on longer spatio-temporal scales. …”
Section: Precipitationmentioning
confidence: 99%